Tensile properties of military chin-strap webbing. Issue 6 (April 2014) - Carr, Debra; Starling, George; Wilton, Thomas de; Horsfall, Ian
Helmet security relies on a retention system that is usually manufactured from webbing. In many helmets (e.g. bicycle, climbing) this is polyester or nylon webbing. In UK military helmets, cotton webbing is currently used for the retention system, including the chin-strap. Cotton is the preferred fiber content rather than a synthetic-polymer fiber due to the potential melt hazard of the latter. Whether the retention system of military helmets is strain rate sensitive at quasi-static and dynamic rates and whether the webbing degrades when exposed to ultraviolet radiation (UVR) are of interest with reference to current conflicts. This paper (i) presents data on quasi-static tensile properties at varying strain rates, (ii) describes a method developed to measure the dynamic tensile strain rate sensitivity and (iii) uses that method to determine the effect of simulated UVR exposure on dynamic tensile properties of cotton webbing typical of that used in UK military helmets.